Eroticism in Modern Javanese Poetry (Geguritan); an Analysis with a Semiotic Approach (Sutasoma : Jurnal Sastra Jawa, 2023)
This article intends to highlight the expressions and depictions of symbols and meanings of eroticism that are present in modern Javanese poetry texts (geguritan) as a form of Javanese literature and cultural products of society. This study seeks to reveal the symbols and meanings of eroticism that are expressed in the text of the modern Javanese poem geguritan entitled "Aku lan Dheweke" by Poer Adhi Prawoto, a poet who is also known as a critic of moderen Javanese literature. The formulation of the problem in this article is 1) How is eroticism expressed in the geguritan “Aku lan Dheweke” by Poer Adhie Prawoto? 2) What are the symbols and meanings implied in the geguritan “Aku lan Dheweke” by Poer Adhi Prawoto? The aims of this article are 1) To describe the form of erotic expression in the geguritan “Aku lan Dheweke” by Poer Adhie Prawoto. 2) Reveal the symbols and meanings implied in the erotic geguritan “Aku lan Dheweke” by Poer Adhi Prawoto. Methodologically the approach used in this research is descriptive qualitative with a paradigm of critical analysis of cultural studies. Qualitative descriptive research reveals the analyzed data by providing detailed and in-depth descriptions of each problem formulation. The theoretical approach uses a semiotic approach. Semiotics is a science or method of analysis to study signs. Signs are tools that we use in trying to find a way in this world, in the midst of humans and with humans. Keywords: Eroticism, Modern Javanese Poetry, Semiotic